Air pollution from natural and anthropic sources and male fertility - Joanna Jurewicz; Emila Dziewirska; Michał Radwan; Wojciech Hanke (BMC, 2018)
Abstract Exposure to air pollution has been clearly associated with a range of adverse health effects, including reproductive toxicity. However, a limited amount of research has been conducted to examine the association between air pollution and male reproductive outcomes, specially semen quality. We performed a systematic review (up to March 2017) to assess the impact of environmental and occupational exposure to air pollution on semen quality. Epidemiological studies focusing on air pollution exposures and male reproduction were identified by a search of the PUBMED, MEDLINE, EBSCO and TOXNET literature bases. Twenty-two studies were included which assess the impact of air pollutants (PM2.5, PM10, SO2, NOx, O3, PAHs) on main semen parameters (sperm concentration, motility, morphology), CASA parameters, DNA fragmentation, sperm aneuploidy and the level of reproductive hormones. The number of studies found significant results supporting the evidence that air pollution may affect: DNA fragmentation, morphology and motility. In summary, most studies concluded that outdoor air pollution affects at least one of the assessed semen parameters. However the diversity of air pollutants and semen parameters presented in the studies included in the review and different study design caused lack of consistency in results and difficulties in comparison.